Self-titration of inhaled corticosteroid and β2-agonist in response to symptoms in mild asthma: a pre-specified analysis from the PRACTICAL randomised controlled trial. Issue 4 (8th October 2020) - Baggott, Christina; Hardy, Jo; Sparks, Jenny; Holliday, Mark; Hall, Daniela; Vohlidkova, Alexandra; Hancox, Robert J.; Weatherall, Mark; Fingleton, James; Beasley, Richard
Introduction: In mild asthma, as-needed budesonide–formoterol is superior or noninferior to maintenance budesonide plus as-needed short-acting β2 -agonist in reducing severe exacerbations. In this pre-specified analysis, we investigated patterns of inhaled corticosteroid (ICS) and β2 -agonist use in PRACTICAL, a randomised controlled trial. Methods: Participants were randomised 1:1 to as-needed budesonide–formoterol (200/6 μg Turbuhaler, one actuation) or maintenance budesonide (200 μg Turbuhaler, one actuation twice a day) with as-needed terbutaline (250 μg, two actuations) for 52 weeks. 110 participants had electronic monitors attached to their study inhalers which captured the time and date of every actuation. Key outcome measures were patterns of ICS and β2 -agonist use. One actuation of budesonide–formoterol was considered to be an equivalent bronchodilator dose as two actuations of terbutaline. Results: Participants randomised to as-needed budesonide–formoterol had more days with no ICS use compared with maintenance budesonide (median total days of no use 156 versus 22 days, respectively), lower median daily budesonide dose (164 versus 328 μg, respectively) and a greater median number of days of ≥4 budesonide actuations (4 versus 1 days, respectively). Participants randomised to as-needed budesonide–formoterol took higher equivalent doses of β2 -agonist both overall (median number of actuations 0.8 versus 0.3 per day, respectively) and in response to worsening asthma (total number of "overuse days" of >8 or >16 actuations of budesonide–formoterol or terbutaline 33 versus 10 days, respectively). Conclusions: The timing of ICS dose when self-titrated to β2 -agonist use is more important than total ICS dose in reducing severe exacerbation risk in mild asthma, when associated with greater overall use of as-needed β2 -agonist. In mild asthma, the timing of the ICS dose, when self-titrated through the vehicle of β2 -agonist reliever use, is more important than total ICS dose in reducing severe exacerbation risk, when associated with greater overall as-needed β2 -agonist use https://bit.ly/2Zs5CJV